Outcome of Malaria Associated Renal Failure (MARF) Treated with Acute Peritoneal Dialysis - Dutta, Prodip Kumar; Chowdhury, Dipti; Yunus, Emran Bin; Kashem, Md Abul; Khan, Md Iftakher Hossain; Huda, Md Nurul; Das, Saibal (Journal of Chittagong Medical College Teachers’ Association, 2010)
Keywords: faciparum malaria; intermittent peritoneal dialysis; multi-organ failure DOI: 10.3329/jcmcta.v20i2.5620 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):16-18